Characterization of composite hydrocolloid films - Garcia, Maria Alejandra (2004)
Chitosan (CH) and methylcellulose (MC) are hydrocolloids with good film-forming properties. The objectives of the present work were to characterize: (i) rheological and surface tension properties of the filmogenic suspensions and (ii) water solubility, color, mechanical properties and water vapor permeability of the composite films. Suspensions of 1 and 2% CH and 1% MC were mixed in different proportions. Surface tension of filmogenic suspensions ranged between 72 and 87.5 dyn cm−1. All suspensions were pseudoplastic; apparent viscosity and consistency index of the mixtures were higher than those of MC or CH suspensions. Films were obtained by casting. Water vapor permeabilities for CH and MC films were 9.03±0.12×10−11 and 7.55±0.60×10−11 g s−1 mPa−1, respectively; intermediate values were obtained for the composite films. CH films showed rigid characteristics (high elastic modulus and small elongation). Film flexibility increased with increasing MC content, the higher elongation and lower elastic modulus of composite films indicated the relevance of hydrocolloid interactions.